Colonization of novel algal habitats by juveniles of a marine tube-dwelling amphipod - Bueno, Marilia; Machado, Glauco B. O. [UNESP]; Leite, Fosca P. P. (Peerj Inc, 2020)
Background: Dispersal is an important process affecting population dynamics and connectivity. For marine direct developers, both adults and juveniles may disperse. Although the distribution of juveniles can be initially constrained by their mothers' choice, they may be able to leave the parental habitat and colonize other habitats. We investigated the effect of habitat quality, patch size and presence of conspecific adults on the colonization of novel habitats by juveniles of the tube-dwelling amphipod Cymadusa filosa associated with the macroalgal host Sargassum filipendula. Methods: We tested the factors listed above on the colonization of juveniles by manipulating natural and artificial plants in both the field and laboratory. Results: In the laboratory, juveniles selected high-quality habitats (i.e., natural alga), where both food and shelter are provided, when low-quality resources (i.e., artificial alga) were also available. In contrast, habitat quality and algal patch size did not affect the colonization by juveniles in the field. Finally, the presence of conspecific adults did not affect the colonization of juveniles under laboratory condition but had a weak effect in the field experiment. Our results suggest that C. filosa juveniles can select and colonize novel habitats, and that such process can be partially affected by habitat quality, but not by patch size. Also, the presence of conspecifics may affect the colonization by juveniles. Successful colonization by this specific developmental stage under different scenarios indicates that juveniles may act as a dispersal agent in this species.
Keywords: Dispersal; Connectivity; Subtidal; Rocky shore; Direct development; Crustaceans